Role of cardiotocography in high risk pregnancy and its correlation with increase cesarean section rate - Gupta, Manisha; Gupta, Punit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: FHR monitoring plays the most important role in management of labouring patient when incidence of fetal hypoxia and progressive asphyxia increases. Now a day’s cardiotocography (CTG) become a popular method for monitoring of fetal wellbeing and it is assisting the obstetrician in making the decision on the mode of delivery to improve perinatal outcome. The aim of the study was to assess the effect of cardiotocography on perinatal outcome and its correlation with caesarean section rate. Methods: In this prospective observational study 201 gravid women with high risk pregnancy in first stage of labour were taken. Result was assessed in the form of Apgar score at five minute, NICU admission, perinatal mortality and mode of delivery. Statistical analysis is done by using Chi square test and p<0.05 is considered as statistically significant. Results: Perinatal morbidity in the form of NICU admission is higher in nonreactive group as compare to reactive group (75.7% v/s 22.8%). Cesarean section rate for fetal distress were higher in nonreactive group (87.8%) in comparison to reactive group (20.5%). So this study suggest that there is significant difference in mode of delivery with increasing chances of caesarean section in cases belong to non-reactive traces (p<0.001). Conclusions: Admission test is non-invasive and the best screening test to evaluate the fetal health and to predict the perinatal outcome but it also associated with increase caesarean section rate.